A scatternet formation algorithm for Bluetooth networks with a non-uniform distribution of devices - Sharafeddine, Sanaa (2012)
We address the problem of scatternet formation for network scenarios with a non-uniform distribution of Bluetooth devices. The assumption of having a non-uniform distribution of devices in a given area of interest is motivated by examples that can be encountered in real scenarios. We propose a new scatternet formation protocol called BlueHRT (Bluetooth Hybrid Ring Tree) that results in a hybrid ring tree topology. The proposed protocol operates in multiple phases that include node discovery, identification of a dense area within the network, role assignment with ring based piconets in the dense area and tree based piconets in the surrounding lightly loaded areas, and interconnection of the piconets to each other via slave–slave and master–slave bridges. General protocol design analysis and ns-2 simulation results are presented in order to highlight the main performance characteristics.